Investigation of novel pharmacological chaperones against gaucher disease - Yılmazer, Büge. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2016., 2016)
Beta-Glucocerebrosidase (GBA) is a lysosomal protein which is responsible for the hydrolysis of glycosylceramide into glucose and ceramide. Mutations in GBA cause a dramatic decrease in activity and lead to accumulation of glycosylceramide with the increase in spleen and liver volumes as well as skeletal deformations, and these symptoms are named as Gaucher Disease. Although enzyme replacement therapies and substrate reduction methods are utilized to overcome Gaucher Disease, they are not enough to treat Gaucher Disease patients, because the disease is neuropathic, and most of the drugs like molecules reported so far fail to pass the blood brain barrier. In this work, we studied pyrrolidine-based compounds with QSAR, Virtual Screening, Glide Docking and MD simulations in order to identify pharmacological chaperones which cross blood brain barrier and stabilize GBA to prevent its degradation in endoplasmic reticulum. New inhibitors PCs were retrieved from ZINC Database using pharmacophore hypotheses of ligand-based and structure-based models. After rigid docking of these molecules at SP and XP modes and filtration with respect to strain energy cutoff and druglikeness properties, top ligands were further examined by induced fit docking. As a result, 7 new compounds that can potentially cross the blood brain barrier were proposed as GBA PCs. Their stabilities were examined by Molecular Dynamic simulations. All compound except compound 6 remained bound to the GBA active site until the end of 50 ns simulation. 3 of these 7 compounds have tricyclic pyrido-thienopyrimidine scaffold and one has dioxino quinolone scaffold. The derivatives of these scaffolds are used as antiallergic agents, antibiotic and anticancer compounds. Now, they may offer a new approach for the treatment of neuropathic Gaucher Disease Type 2 and Type 3.
Keywords: Gaucher's disease.